Estudos ecológicos da comunidade planctônica de vinte e cinco ecossistemas aquáticos temporários tropicais - Passos, Rodrigo Ferroni (2017)
Ecological studies were carried out in twenty-five natural temporary aquatic environments, located in the cities of Urucuia, Lagoa Grande and Pirapora, in the north and northwest of the state of Minas Gerais, Brazil. In each environment, collections were carried out in April 2015, May 2016 and January 2017, during which limnological variables were measured and samples from the phytoplankton (qualitative) and zooplankton (qualitative and quantitative) communities, as well as from sediment, were collected. Experiments were also carried out in the laboratory to evaluate the effects of different temperatures and luminosity on the hatching of diapause eggs of zooplankton species present in these environments. In general, the values obtained for the physical and chemical variables of the studied environments were in a favorable range to the development of the phytoplankton community. However the low concentration of chlorophyll a and the low richness of phytoplankton species may be reflections of the low water transparency, and the turbidity may limit the growth of the phytoplankton. Qualitative and quantitative analyzes of the zooplankton community indicated low species richness in these ponds. Although Rotifera presented a greater richness of taxa, Copepoda Cyclopoida was the most abundant and numerically representative group. The presence or absence of the Anostraca Dendrocephalus brasiliensis does not seem to interfere in the composition and density of the zoplanktonic community. Species richness and local diversity should be related to disturbances and environmental dynamics. The results obtained in the experiment of hatching of zooplankton diapause eggs showed that the different ponds have similar hatching values, and low temperatures (20°C) and absence of light have a negative influence on hatching these eggs. In addition, it was observed that higher temperatures (35°C) accelerated the hatching of the diapause eggs during the first days of incubation. Thus we can infer that, in general, zooplankton community present in all the studied temporary aquatic environments behave in a similar way.